Language choice and use of Malaysian public university lecturers in the education domain - Tam, Lee Mei; Abdullah, Ain Nadzimah; Chan, Swee Heng; Mohd Kasim, Zalina (Australian International Academic Centre, 2016)
It is a norm for people from a multilingual and multicultural country such as Malaysia to speak at least two or more languages. Thus, the Malaysian multilingual situation resulted in speakers having to make decisions about which languages are to be used for different purposes in different domains. In order to explain the phenomenon of language choice, Fishman domain analysis (1964) was adapted into this research. According to Fishman’s domain analysis, language choice and use may depend on the speaker’s experiences situated in different settings, different language repertoires that are available to the speaker, different interlocutors and different topics. Such situations inevitably cause barriers and difficulties to those professionals who work in the education domain. Therefore, the purpose of this research is to explore the language choice and use of Malaysian public university lecturers in the education domain and to investigate whether any significant differences exist between ethnicity and field of study with the English language choice and use of the lecturers. 200 survey questionnaires were distributed to examine the details of the lecturers’ language choice and use. The findings of this research reveal that all of the respondents generally preferred to choose and use English language in both formal and informal education domain. Besides, all of the respondents claimed that they chose and used more than one language. It is also found that ethnicity and field of study of the respondents influence the language choice and use in the education domain. In addition, this research suggested that the language and educational policy makers have been largely successful in raising the role and status of the English language as the medium of instruction in tertiary education while maintaining the Malay language as having an important role in the communicative acts, thus characterizing the lecturers’ language choice and use.